2015
DOI: 10.1186/s12879-015-0760-z
|View full text |Cite
|
Sign up to set email alerts
|

Orbital apex syndrome: an unusual complication of herpes zoster ophthalmicus

Abstract: BackgroundHerpes zoster ophthalmicus is defined as herpes zoster involvement of the ophthalmic division of the trigeminal nerve. Ocular involvement occurs in 20–70% of patients with herpes zoster ophthalmicus and may include blepharitis, keratoconjunctivitis, iritis, scleritis, and acute retinal necrosis. Orbital apex syndrome is a rare but severe ocular complication of herpes zoster ophthalmicus. We present here the first reported case of herpes zoster ophthalmicus complicated by orbital apex syndrome in a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 17 publications
4
52
0
3
Order By: Relevance
“…However, her cataract worsened, which may be a complication of uveitis or due to prolonged corticosteroid usage. She also had persistent anisocoria, as described in other reports [11], [13]. Our patient’s optic nerve function tests are within normal limits, and her optic disc remains pink.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, her cataract worsened, which may be a complication of uveitis or due to prolonged corticosteroid usage. She also had persistent anisocoria, as described in other reports [11], [13]. Our patient’s optic nerve function tests are within normal limits, and her optic disc remains pink.…”
Section: Discussionsupporting
confidence: 86%
“…Lee et al reported orbital myositis and enhancement of the retro-orbital optic nerve sheath on MRI in their case of orbital apex syndrome following herpes zoster ophthalmicus [13]. Diffuse inflammation of the orbital cavity, ocular muscles, and optic nerve on the affected side was also described by Shirato et al [11].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present case report, MRI typically shows diffuse enhancement of the orbital apex involving the optic nerve, extraocular muscles are swollen, consistent with myositis (3,5,9,10,12,13).…”
Section: Patient Evaluationmentioning
confidence: 71%
“…Recently, in addition to meningitis and meningoencephalitis, Ramsey-Hunt syndrome, namely a cervical node ganglionitis, has often begun to be diagnosed, development of which can lead to paralysis of facial muscles and reduced hearing abruption [27]. The development of ophthalmic herpes, in which a complete loss of vision is possible due to lesion of the optic nerve and its atrophy, deserves particular attention [28]. No less widespread complication of shingles is postherpetic neuralgia, which can persist for several months after regression of rash, and often leads to a reduction in ability, and in some cases, to a person's disability [29].…”
Section: Discussionmentioning
confidence: 99%